Paradigm of spiritual growth of an individual: Theoretical concepts - Vasyl Fazan; Tetiana Fazan; Kristina Taranenko; Vitaliy Nikolenko (Educational Challenges)
Purpose. The purpose of the article is to analyze the theoretical concepts of the paradigm of spiritual growth of an individual through the systematization of the main approaches, conditions, and factors that characterize the process under study.